Acceptable deviation of labial tubercle and anterior tooth midlines relative to facial midline in smile aesthetics: A retrospective observational study. Issue 41 (14th October 2022) - Wang, Xiuhong; Long, Jinlie; Mei, Mei; Huang, Jin; Chen, Yuan; Zhou, Yuanzhong; Zhang, Jiangtao
Abstract : Smile aesthetics are mainly influenced by the relative position of facial midline (FC-line), anterior tooth midline (AT-line) and labial tubercle midline (LT-line). However, the acceptable deviation of LT-line and AT-line relative to FC-line is unknown. This study aims to fill the critical gap. We adopted the method of cross-sectional study, the frontal full-face smile photographs of 1 subject set (1 male) were enrolled. Taking the FC-line as the center line, twelve images with 1-mm increment relative to FC-line (right or left deviation, the maximum deviation distance was 3-mm) in LT-line deviation model or LT + AT-line deviation model (LT-line coincided with AT-line basing on LT-line deviation model) were produced. Basing on Q-sort assessment, the images were evaluated by 160 dentists, 165 orthodontic patients and 163 freshmen. And the collected Q-sort scores were subjected to nonparametric comparative analysis using SPSS 18.0. There were significant differences in Q-sort scores among different groups ( P  < .01). When the deviation distance was 1 mm in dentist and orthodontic patient or 2 mm in freshman group, there was no significant difference in smile attractiveness scores between the LT line deviation model and the LT + AT line deviation model ( P  > .05). We also found that the score of male dentist significantly higher than female dentist ( P  < .05). However, the scores of right deviation in dentists and orthodontic patients were significantly lower than those in left deviation ( P  < .05). The acceptable deviation of LT-line and AT-line relative to FC-line should be kept within 2 mm. Besides, raters' occupation and gender, and deviation direction of model may influence the smile aesthetics.